1977
DOI: 10.1111/j.1476-5381.1977.tb06982.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Radioactive Cardiac Glycosides by Various Brain Regions in Relation to the Dysrhythmogenic Effect

Abstract: 1 Ouabain was administered at a loading dose of 3 jg/kg followed by an infusion at a rate of 1 jig kg-1 min-' in order to produce severe dysrhythmia in dogs within 60 minutes. Similarly, digitoxin at a loading dose of 9 jg/kg followed by an infusion at a rate of 3 ,ug kg-' min-' was administered to compare its effect with that of ouabain. 2 During the 60 min experimental period, the plasma concentrations gradually rose with the continuous infusion of these drugs. However, in comparison to the 60 min plasma val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…The concentration of digitoxin in the medulla and midbrain at 1 hour (A) after the injection was lower than the concentration in the blood . These data are in good agreement with the results reported by Weaver et al (9) and Dutta et al (10). As shown in the table, the total digitoxin concentration of both blood and the heart decreased to one third at 48 hours after the injection compared to the value at 1 hour after the injection.…”
supporting
confidence: 93%
“…The concentration of digitoxin in the medulla and midbrain at 1 hour (A) after the injection was lower than the concentration in the blood . These data are in good agreement with the results reported by Weaver et al (9) and Dutta et al (10). As shown in the table, the total digitoxin concentration of both blood and the heart decreased to one third at 48 hours after the injection compared to the value at 1 hour after the injection.…”
supporting
confidence: 93%
“…We do not believe that aminophylline toxicity results from a 'toxic' blood level, hut from a 'toxic' level in a specific tissue such as in the Purkiri,je fiber (Moore et ol.,3986) or possibly even the area postrema (Dutta et al, 1977). I t is thought that ventricular arrhythmias resulting from increased automaticity arise from Purkinje fibers, and that ventricular arrhythmias resulting from digitalis toxicity arise from effects of the glycoside on the area postrema and/or Purkinje fibers in which oscillatory after potentials develop.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Donaldson et al (1972) also observed accumulation of radioactivity in the medulla of the rat following intraventricular injection of 3H-ouabain. Dutta et al (1977) and Bass et al (1982) have suggested that small but physiologically significant local concentrations of cardiac glycoside in brain may have been undetected in some studies owing to dilution in large tissue samples. The results reported by Donaldson et al (1972), Frazier andBinnion (1981), our previous results (Bass et al, 1982), and those of the present study suggest that blood-borne cardiac glycoside may reach cardiovascular centers in the medulla through the area postrema, which lacks a blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported data suggesting that the blood-brain barrier effectively prevents the penetration of cardiac glycosides into the brain (Oldendorf, 1974;Dutta et al, 1977) and have concluded that cardiac glycosides have no significant direct effect on central neurons associated with cardiovascular regulation Dutta et al, 1977;Weaver et al, 1977).…”
mentioning
confidence: 99%